UPAYA MENINGKATKAN KEMAMPUAN LITERASI NUMERASI PESERTA DIDIK KELAS V DENGAN PEMBELAJARAN PROBLEM BASED LEARNING DI SD NEGERI TUNJUNGSEKAR 1 - Rohmah, Nurlia Ni’matur; Iin Hindun (Al-Ihda' : Jurnal Pendidikan dan Pemikiran, 2024)
The development of the current digital era makes literacy and numeracy of human resources a competency that needs to be mastered. However, the level of literacy in Indonesia is still below average. This is shown by the evidence that most students from class V SD Tunjungsekar 1 did not succeed in achieving the minimum score that has been set, especially in learning mathematics. Therefore, researchers applied PBL (Problem Based Learning) to improve numeracy literacy skills, especially for fifth grade students of SD Tunjungsekar 1. This study used qualitative and quantitative methods. The process of obtaining data is done through observation and interviews that produce numerical data which is analysed to conclude the results of the study. The implementation of this study showed success as evidenced by the increase in the scores of grade V students after the PBL learning method so that it can be concluded that Problem Based Learning applied by researchers succeeded in improving the literacy skills of grade V students of SD Tunjungsekar 1